Woody plant communities in the Philippine teak forest landscape along Verde Island Passage, Batangas, Luzon, Philippines - Anacleto Macatangay Caringal; INOCENCIO Jr BUOT; ELAINE LOREEN C. VILLANUEVA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Caringal AM, Buot IE Jr, Villanueva ELC. 2019. Woody plant communities in the Philippine teak forest landscape along Verde Island Passage, Batangas, Luzon, Philippines. Biodiversitas 20: 3189-3198. The study described the communities of woody plants in a semi-evergreen tropical forest dominated by endemic Philippine teak (Tectona philippinensis Benth. & Hook. f, Lamiaceae) and determined the local environmental factors affecting the distribution of dominant woody species across the Philippine teak forest (PTF) landscape. The Philippine teak is a Critically Endangered species according to the International Union for the Conservation of Nature (IUCN). Quantitative dominance analysis of arboreal vegetation data (basal area and relative dominance) from 24 (20m x 20m) sampling plots generated the cluster dendrogram, while Canonical Correspondence Analysis (CCA) was performed for 47 woody species and habitat-environment variables. As a result, four vegetation zones were named: (I) pure stand of Tectona philippinensis, (II) mixed T. philippinensis-Garuga floribunda-Terminalia polyantha, (III) mixed Celtis latifolia-T. philippinensis and (IV) mixed Tamarindus indica-Xylocarpus rumphii. These zones were governed more by physiographic (altitude ) and edaphic influences of predominantly agro-coastal landscapes. The environmental variables were essential in verifying not only the association of dominant tree flora in the local landscape but also provide insight for forest management zoning and the ecological requirements of the tree species for in-situ and ex-situ biodiversity conservation.